Private Solutions for Infrastructure : Opportunities for the Philippines - Public-Private Infrastructure Advisory Facility (Washington, DC: World Bank, 2013)
This Country Framework Report for the Philippines is one of the first in a series of country reviews aimed at improving the environment for private sector involvement in infrastructure. Prepared at the request of the Philippine Government, the report has three main objectives: 1) To describe and assess the current status and performance of key infrastructure sectors. 2) To describe and assess the policy, regulatory, and institutional environment for involving the private sector in those sectors. 3) Through the above, to assist policymakers in framing future reform and development strategies and to assist potential private sector investors in assessing investment opportunities.